Blueberry Polyphenol Extracts Enhance the Intestinal Antioxidant Capacity in Weaned Rats by Modulating the Nrf2–Keap1 Signal Pathway - Zhao, Fangfang; Yan, Shen; Tian, Mengliang (Frontiers in Physiology, 2021)
Weaning causes the generation of excessive reactive oxygen species in the body, which could lead to oxidative stress. Polyphenols, for which blueberries are an important dietary source, are known for various health benefits including antioxidant properties. Here, we sought to elucidate the effects of blueberry polyphenol extracts (BPE) on intestinal antioxidant capacity and possible underlying mechanisms in weaned rats. Ninety-six rats were assigned to two groups and fed either a standard diet or a standard diet supplemented with BPE (200 mg/kg). The results showed that BPE supplementation increased (P < 0.05) catalase and superoxide dismutase activities and decreased (P < 0.05) interleukin-1 and interferon-γ contents in the jejunum and ileum. The abundances of mammalian target of rapamycin, ribosomal p70 S6 kinase and eukaryotic initiation factor 4E-binding protein 1 mRNA were elevated in the jejunum and ileum (P < 0.05) after BPE supplementation. Additionally, BPE supplementation decreased (P < 0.05) Kelch-like ECH-associated protein 1 (Keap1) gene transcription and enhanced (P < 0.05) NF-E2-related factor 2 (Nrf2) gene transcription in the jejunum and ileum. According to our results, BPE-induced protective effects against oxidative stress appear through the promotion of the jejunal and ileal antioxidant defence system in weaned rats, which was associated with the Nrf2–Keap1 signalling pathway.